The Relationship between Spiritual Intelligence and Resiliency of Rehabilitation Staff - Ebrahimi Barmi, Banafsheh; Hosseini, Mohammadali; Abdi, Kianoush; Bakhshi, Enayatollah; Shirozhan, Shima (2019)
This research aims to determine the relationship between spiritual intelligence and resiliency of rehabilitation staff. The reliable and validated spiritual intelligence and CD-RISC resiliency and demographic scales were used to collect data. There is a significant relationship between spiritual intelligence and the resiliency of rehabilitation staff (r = 0.38). Results showed that by increasing spiritual intelligence, resilience could increase.
Keywords: Staff; Rehabilitation; Resiliency; Spiritual Intelligence